Bypass lateral esophagostomy - Ellenbogen, Germano; Pinotti, Henrique Walter; Molina Rivadeneira, Galo; Raia, Arrigo (Cirugía del Uruguay, 1982)
The authos presente a new te chnique in esophagostomy, associated with an endoscopic method far the surgicl approach of the cevical reion; uing the igid 8 x 45 Chevalier-Jackson esophagoscope, of which the distal extremity guides the surgeon to perfonn the incision on the left cevical region in the under!ying esophagus; through which the endosopic plies are exteiozed and ued to pull the previously prepred Foley's probe No. 22 into the esophagus.